Phytochemical and Antimicrobial Screening of Native Plant Swertia chirayita (Roxb. ex Fleming) Karst from Rasuwa district of Nepal - Ishwar Subedi; Tika Bahadur Karki (Journal of Tropical Life Science, 2018)
Swertia chirayita is one of the highly traded medicinal plants of Nepal. This plant was chosen for investigation as folk medicines and then collected from the diverse habitats of Rasuwa district of Nepal and specimens have been checked and identified at National Herbarium and Plant Laboratories (NHPL), Godavari, Lalitpur. The identified plant was subjected to study physiochemical and biological activity. The stem, root and leaves of the plant were dried, made powder and mixed at the ratio of 1 : 1 : 1 and then extracted using methanol solvent by cold and warm method. The percentage yield from the plant was highest in warm methanol with 3.73%, followed by cold methanol with 2.28%. Plant extract showed the presence of phytochemicals like basic alka-loids, coumarin, glycosides, steroids, quinones, flavonoid and terpenoids. The antibacterial activity of the ex-tract showed significant bioactive by inhibiting the growth of selected pathogenic microbial species for the test. The zone of inhibition (ZOI) shown by the extracts was comparable to the standard antibiotics. Similar-ly, proximate composition was also carried out. The antioxidant activity of the sample was found to be 62.54% at 500 Âµg/mL and 15.32% at 100 Âµg/mL by radical scavenging method and showed significant antioxi-dants potential.Â